Simple electrodiagnostic method for morton neuroma. Issue 2 (26th June 2013) - Aydinlar, Elif Ilgaz; Uzun, Metin; Beksac, Burak; Ozden, Vahit Emre; Karaarslan, Ercan; Oge, A. Emre
ABSTRACT Introduction: We describe a simple and quickly applied electrodiagnostic method for confirming the diagnosis of interdigital neuropathy caused by Morton neuroma (MN). Methods: Interdigital nerves II–III and III–IV were stimulated with surface electrodes simultaneously touching the lateral side of 1 toe and the medial side of the other. Recording was also made with surface electrodes. The results of 20 normal controls and 14 patients with MN were evaluated. Results: The amplitude and peak latency values elicited in the patients as well as the interside differences revealed an acceptable abnormality rate between 57.1% and 71.4%. Conclusions: Although the most popular and effective method of MN diagnosis is clinical evaluation supported by imaging, electrophysiological studies can, in selected patients, provide valuable information. Muscle Nerve49: 193–197, 2014